An Analysis of the Violations of Cooperative Principle in the Weekly Humor (Humor Pekan ini ) in Pikiran Rakyat News Paper - Dina Rachmawati (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
Jokes are CP-violating Text, and at least violate one maxim of Grice’s Cooperative Principle. This study found that maxim of Manner and maxim of Quality are the most common places for the violation. Jokes violated the CP by giving obscure expression, unnecessary prolixity, and by giving false evidence/fact.  The study concludes that the first, violations are manipulated to provoke laughter and amusement. Second, both jokes producer and readers share the same common knowledge. Keywords: Gricean Principle, Cooperative Principle, Jokes